Polish Migrant Parents of Secondary School Boys in the United Kingdom. Issue 3 (2nd July 2016) - Tkacz, Daria; McGhee, Derek
ABSTRACT: This article focuses on the parents of secondary school Polish boys and their capacity to realise their educational and professional aspirations for their children. Our primary finding is that although many Polish parents face considerable challenges in manoeuvring through the educational system, some Polish parents display a level of agency comparable to that of white, British middle-class parents.